Product Rule
  |
\[
\begin{aligned}
\Delta (ab)_n &= a_n \Delta b_n + b_n \Delta a_n + \Delta a_n \Delta b_n \\
\triangledown (ab)_n &= a_n \triangledown b_n + b_n \triangledown a_n - \triangledown a_n \triangledown b_n \\
\\
\Delta (uv) &= u \Delta v + Ev \Delta u \\
\end{aligned}
\] |
If \(a\) is a polynomial of degree \(p\), then
  |
\[
\begin{aligned}
\Delta^{p+1} a &= (0) \\
\end{aligned}
\] |
Falling Power Rule
  |
\[
\begin{aligned}
n^{\underline k} &= n (n-1) \cdots (n-k+1), \hskip4em n^\underline{0} = 1 \\
\Delta n^{\underline k} &= k \, n ^{\underline{k-1}}\\
n^{- \underline k} &= \frac{1}{(n+1) (n+2) \cdots (n+k)} \\
\end{aligned}
\] |
Sequence operators
  |
\[
\begin{aligned}
(Ia)_n &= a_n \\
(Ea)_n &= a_{n+1} \\
(\Delta a)_n &= a_{n+1} - a_n, \hskip4em \Delta = E - I \\
(\triangledown a)_n &= a_n - a_{n-1}, \hskip4em \triangledown = I - E^{-1} \\
(\triangledown \Delta a)_n &= a_{n+1} - 2a_n + a_{n-1}, \hskip1em \text{second central difference} \\
\triangledown \Delta \, a &= \Delta \triangledown a \\
\end{aligned}
\] |
Higher Derivatives
  |
\[
\begin{aligned}
\Delta^k &= (E - I)^k = \sum_{i=0}^k (-1)^{k-i} {k \choose i} E^i \\
\end{aligned}
\] |
Anti-difference
  |
\[
\begin{aligned}
\Delta^{-1} &= (E - I)^{-1} = -(I - E)^{-1} = -(I + E + E^2 + E^3 + \cdots) + C \\
\end{aligned}
\] |
so long as the sequence \(a_n\) is eventually 0
Discrete Fundamental Theorem of Integral Calculus
  |
\[
\begin{aligned}
\sum_{n=A}^B \Delta u &= u \, \bigg \rvert_{n=A}^{B+1} \\
\sum_{n=A}^B \triangledown u &= u \, \bigg \rvert_{n=A-1}^{B} \\
\end{aligned}
\] |
Alternatively,
  |
\[
\begin{aligned}
\sum_{n=A}^B u &= \Delta^{-1} u \, \bigg \rvert_{n=A}^{B+1} \\
\sum_{n=A}^B u &= \triangledown^{-1} u \, \bigg \rvert_{n=A-1}^{B} \\
\end{aligned}
\] |
Integration by parts
  |
\[
\begin{aligned}
\Delta (uv) &= u \Delta v + Ev \Delta u \\
\sum_{n=A}^B u \Delta v &= uv \, \bigg \rvert_{n=A}^{B+1} - \sum_{n=A}^B Ev \Delta u \\
\end{aligned}
\] |
Differential equations
Linear first-order recurrence relation:
  |
\[
\begin{aligned}
u_{n+1} &= \lambda u_n \\
E \, u &= \lambda u \\
(E - \lambda \, I) \, u &= 0 \\
\implies u_n &= u_0 \, \lambda^n \\
\end{aligned}
\] |
Linear first-order difference equation:
  |
\[
\begin{aligned}
\Delta u &= \lambda u \\
(E - I) \, u &= \lambda u \\
(E - (\lambda + 1) \, I) \, u &= 0 \\
\implies u_n &= u_0 \, (\lambda + 1)^n \\
\end{aligned}
\] |
Numerical ODE's
Many differential equations of the form
\(\displaystyle \frac{dx}{dt} = f(x,t) \)
cannot be solved exactly. Hence the use of numerical ODE's to approximate a solution.
Euler's method
Uses a difference equation to approximate the solution of an initial value problem. Essentially it's Taylor series 1st order approximation for the recursion relation.
Given
\(\displaystyle \frac{dx}{dt} = f(x,t) \)
, and initial value
\( x_0 = x(t_0) \)
, Euler's method approximates \( x(t_*) \) for some \(t_* > t_0 \).
  |
\[
\begin{aligned}
x_{n+1} = x_n + h\,f(x_n, t_n) \\
t_{n+1} = t_n + h \\
h = \frac{t_* - t_0}{N} \\
\end{aligned}
\] |
where N is the number of intervals.
Numerical Integration
How to approximate the definite integral \(\displaystyle \int_a^b f(x)\,dx\) via finite sums which approximates the area under the curve ? Common techniques: Riemann sums, trapezoid rules and Simpson's rule.
Left Riemann Sum
  |
\[
\begin{aligned}
\int_a^b f(x)\,dx \approx \sum_{n=0}^{N-1} f_n \cdot (\Delta x)_n = \sum_{n=0}^{N-1} f_n \cdot (x_{n+1} - x_n) \\
\end{aligned}
\] |
Right Riemann Sum
  |
\[
\begin{aligned}
\int_a^b f(x)\,dx \approx \sum_{n=1}^{N} f_n \cdot (\triangledown x)_n = \sum_{n=1}^{N} f_n \cdot (x_n - x_{n-1}) \\
\end{aligned}
\] |
Trapezoid Rule
An improvement over the left and right Riemann sums by averaging them.
  |
\[
\begin{aligned}
\int_a^b f(x)\,dx \approx \sum_{n=0}^{N-1} \frac{1}{2} (f_n + f_{n+1}) \cdot (\Delta x)_n = \sum_{n=0}^{N-1} \frac{1}{2} (f_n + f_{n+1}) \cdot (x_{n+1} - x_n) \\
\end{aligned}
\] |
If sample points are evenly spaced:
  |
\[
\begin{aligned}
\int_a^b f(x)\,dx \approx h \, \bigg(\frac{1}{2}(f_0 + f_N) + \sum_{n=1}^{N-1} f_n \bigg) \\
\end{aligned}
\] |
where \(\displaystyle h = \frac{b-a}{N} \)
# posted by rot13(Unafba Pune) @ 5:18 PM